Chymotrypsin C (CTRC) variants that diminish activity or secretion are associated with chronic pancreatitis - Rosendahl, Jonas; Witt, Heiko; Szmola, Richárd; Bhatia, Eesh; Ózsvári, Béla; Landt, Olfert; Schulz, Hans-Ulrich; Gress, Thomas M; Pfützer, Roland; Löhr, Matthias; Kovacs, Peter; Blüher, Matthias; et al. (Nature genetics, 2008)
Chronic pancreatitis is a persistent inflammatory disease of the pancreas, in which the digestive protease trypsin has a fundamental pathogenetic role. Here we have analyzed the gene encoding the trypsin-degrading enzyme chymotrypsin C ( CTRC ) in German subjects with idiopathic or hereditary chronic pancreatitis. Two alterations in this gene, p.R254W and p.K247_R254del, were significantly overrepresented in the pancreatitis group, being present in 30 of 901 (3.3%) affected individuals but only 21 of 2,804 (0.7%) controls (odds ratio (OR) = 4.6; confidence interval (CI) = 2.6–8.0; P = 1.3 × 10 −7 ). A replication study identified these two variants in 10 of 348 (2.9%) individuals with alcoholic chronic pancreatitis but only 3 of 432 (0.7%) subjects with alcoholic liver disease (OR = 4.2; CI = 1.2–15.5; P = 0.02). CTRC variants were also found in 10 of 71 (14.1%) Indian subjects with tropical pancreatitis but only 1 of 84 (1.2%) healthy controls (OR = 13.6; CI = 1.7–109.2; P = 0.0028). Functional analysis of the CTRC variants showed impaired activity and/or reduced secretion. The results indicate that loss-of-function alterations in CTRC predispose to pancreatitis by diminishing its protective trypsin-degrading activity.